The screen of the haunted mask - "Stine, R.L" (Scholastic Inc.: New York, 2008)
"What should Carly Beth be for Halloween this year? Terrified! Late at night, an ugly green mask is mysteriously calling out to her, and ugly green masks don't like to be ignored"--Page 4 of cover
Keywords: Horror fiction